Levoketoconazole in the Treatment of Patients With Cushing’s Syndrome and Diabetes Mellitus: Results From the SONICS Phase 3 Study - Pivonello, Rosario; Elenkova, Atanaska; Fleseriu, Maria; Feelders, Richard A.; Witek, Przemyslaw; Greenman, Yona; Geer, Eliza B.; Perotti, Paola; Saiegh, Leonard; Cohen, Fredric; Arnaldi, Giorgio (Frontiers in Endocrinology, 2021)
Background: Cushing’s syndrome (CS) has numerous comorbidities, including diabetes mellitus (DM). Levoketoconazole, an orally administered ketoconazole stereoisomer, is in clinical trials for the treatment of CS. Methods: SONICS, a prospective, open-label, phase 3 study in adults with confirmed CS and mean 24-hour urinary free cortisol (mUFC) ≥1.5x ULN, included dose-titration, 6-month maintenance, and 6-month extension phases. This subanalysis evaluated the efficacy of levoketoconazole in patients with DM (n = 28) or without DM (n = 49) who entered the maintenance phase. Safety was evaluated in the overall population (N = 94) during the dose-titration and maintenance phases. Results: Normalization of mUFC at the end of maintenance phase (EoM), without a dose increase during maintenance (SONICS primary endpoint) was observed in 46% of patients with DM (95% CI, 28% to 66%; P = 0.0006 vs null hypothesis of ≤20%) and 33% of patients without DM (95% CI, 20% to 48%; P = 0.0209). At EoM, mean HbA1c decreased from 6.9% at baseline to 6.2% in patients with DM and from 5.5% to 5.3% in patients without DM. Mean fasting blood glucose decreased from 6.85 mmol/L (123.4 mg/dL) to 5.82 mmol/L (104.9 mg/dL) and from 5.11 mmol/L (92.1 mg/dL) to 4.66 mmol/L (84.0 mg/dL), in patients with and without DM, respectively. Adverse events that were more common in patients with DM included nausea (58.3%), vomiting (19.4%), and urinary tract infection (16.7%); none prompted study drug withdrawal. Conclusions: Treatment with levoketoconazole led to sustained normalization of mUFC and improvement in glycemic control that was more pronounced in patients with DM. Clinical Trial Registration: NCT01838551